ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHASILAN UMKM DEPOT AIR MINUM ISI ULANG - Joenoes, A Z. Qais; Effendy, Jani; Tahapary, Grace Hobertina (Jurnal Cita Ekonomika, 2023)
This research aims to determine the analysis of the influence of factors that influence income in several Micro, Small and Medium Enterprises (MSMEs) mini refill water depots in Nusaniwe District, Ambon City. Quantitative descriptive research method with a population of 52 MSMEs in refill drinking water depots, using saturated samples, primary data types were taken using a questionnaire method, data analysis techniques using multiple regression with the help of EViews 12. The results of this research state that partially it shows that capital and time business has a positive and significant effect on the income of air refill depot MSMEs, while business time allocation has a negative and significant effect on the income of refill air depot MSMEs.